Liquid biopsy-based early tumor and minimal residual disease detection: new perspectives for cancer predisposition syndromes - Bohaumilitzky, Lena; Gebert, Johannes; Knebel Doeberitz, Magnus von; Kloor, Matthias; Ahadova, Aysel (Medizinische Genetik, 2023)
Genetic predisposition is one of the major measurable cancer risk factors. Affected patients have an enhanced risk for cancer and require life-long surveillance. However, current screening measures are mostly invasive and only available for certain tumor types. Particularly in hereditary cancer syndromes, liquid biopsy, in addition to monitoring therapy response and assessing minimal residual disease, holds great potential for surveillance at the precancerous stage and potentially even diagnostics. Exploring these options and future clinical translation could help reduce cancer risk and mortality in high-risk individuals and enhance patients’ adherence to tailored surveillance protocols.